PENGARUH DISIPLIN DAN KOMPENSASI TERHADAP KINERJA PEGAWAI DINAS KOPERASI DAN UMKM KAB. LEBAK - Rohmatulloh, Puri; Budiman, Budiman; Mukti, Muhi (Universitas La Tansa Mashiro, 2023)
Study aims to determine the effect of discipline and compensation on employee performance in the Department of Cooperatives and UKM, Lebak Regency. The research method used in this research is quantitative. The data used is primary data originating from distributing questionnaires to employees of the Office of Cooperatives, Small and Medium Enterprises of Lebak Regency, totaling 36 respondents. Data processing is carried out using SPSS 20 software. Based on multiple linear regression analysis and hypothesis testing using the t test and F test. These results indicate that partially discipline has a significant effect on employee performance with the tcount value of the discipline variable (X1) having a significant effect on performance employee (Y). With a tcount and ttable value of 4.506 > 2.034 with a significant level of 0.000 < 0.05. The compensation variable (X2) has a significant effect on employee performance (Y), with a tcount and ttable value of 2.490 > 2.034 a significant level of 0.003 < 0.05. The discipline variable (X1) and compensation (X2) have a simultaneous effect, with Fcount and Ftable of 87.210 >3.28. With a significant level of 0.000 <0.05.